2018
DOI: 10.1177/0269215518815218
|View full text |Cite
|
Sign up to set email alerts
|

The effect of group exercises on balance, mobility, and depressive symptoms in older adults with mild cognitive impairment: a randomized controlled trial

Abstract: Objective: To determine the effects of group exercises on balance, mobility, and depressive symptoms in community-dwelling older adults with mild cognitive impairment. Design: Single blinded, randomized, matched pairs clinical trial. Setting: Four primary healthcare units. Subjects: Fifty-two sedentary subjects with mild cognitive impairment were paired (age, sex, body mass index, and Addenbrooke’s Cognitive Examination Revised score), tested, and then randomized into an intervention group (n = 26) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…In another study with frail and pre-frail older adults, physical exercise was effective in significantly reducing the depression score ( Ng et al, 2017 ). Langoni et al (2019) developed a 24-weeks intervention with 52 mild cognitively impaired and sedentary older adults. Results demonstrated that the program reduced the median geriatric depression score against the initial value.…”
Section: Discussionmentioning
confidence: 99%
“…In another study with frail and pre-frail older adults, physical exercise was effective in significantly reducing the depression score ( Ng et al, 2017 ). Langoni et al (2019) developed a 24-weeks intervention with 52 mild cognitively impaired and sedentary older adults. Results demonstrated that the program reduced the median geriatric depression score against the initial value.…”
Section: Discussionmentioning
confidence: 99%
“…The inception of balance rehabilitation studies in MCI was in the beginning of the last decade (Table 1). There has been an increase in published studies since 2011, with most studies published in 2016 (n = 5) [44,[49][50][51]57] and 2019 (n = 4) [41,43,54,55].…”
Section: Year Of Publicationmentioning
confidence: 99%
“…There were a total of 16 original RCTs [39][40][41][42][43][44]46,47,49,50,53,54,[56][57][58][59]; five studies [45,48,51,52,55] were secondary reports of the 16 RCTs (Table 1). Therefore, in the following sections, the study percentages demonstrating study outcomes and results (Sections 3.1.7 and 3.2) were taken out of the 21 studies, while the study percentages describing other study characteristics (Sections 3.1.3-3.1.6 and 3.1.8) were taken out of the 16 original RCTs.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations